+) \(B=2x^2-4x+1\)
\(\Leftrightarrow B=2\left(x^2-2x+\frac{1}{2}\right)\)
\(\Leftrightarrow B=2\left(x^2-2x+1-\frac{1}{2}\right)\)
\(\Leftrightarrow B=2\left(x-1\right)^2-1\ge-1\)
Min B = -1 \(\Leftrightarrow x-1=0\Leftrightarrow x=1\)
B = 2x2 - 4x + 1
= 2( x2 - 2x + 1 ) - 1
= 2( x - 1 )2 - 1 ≥ -1 ∀ x
Dấu "=" xảy ra khi x = 1
=> MinB = -1 <=> x = 1
D = -3x2 - 6x + 9 ( vầy chứ nhỉ ? )
= -3( x2 + 2x + 1 ) + 12
= -3( x + 1 )2 + 12 ≤ 12 ∀ x
Dấu "=" xảy ra khi x = -1
=> MaxD = 12 <=> x = -1
a,\(2x^2-4x+1\)
\(=2\left[\left(x^2-2x+1\right)-\frac{1}{2}\right]\)
\(=2\left(x-1\right)^2-1\ge-1\forall x\)
Dấu"="xảy ra khi \(2\left(x-1\right)^2=0\Rightarrow x=1\)
Vậy \(Min_B=-1\Leftrightarrow x=1\)
\(\)
Bài làm :
Ta có :
B = 2x2 - 4x + 1
B= 2( x2 - 2x + 1 ) - 1
B= 2( x - 1 )2 - 1 ≥ -1 với mọi x
Dấu "=" xảy ra khi : 2(x-1)2 =0 <=> x = 1
Vậy GTNN của B là : -1 khi x=1
D = -3-6x+9 hình như sai đề
\(B=2x^2-4x+1=2\left(x^2-2x+1\right)-1=2\left(x-1\right)^2-1\)
Vì \(2\left(x-1\right)^2\ge0\forall x;2\left(x-1\right)^2-1\ge-1\)
Vậy GTNN B là -1 <=> x - 1 = 0 <=> x = 1
\(D=-3x^2-6x+9=-3\left(x^2+2x+1\right)+12=-3\left(x+1\right)^2+12\)
Vì \(-3\left(x+1\right)^2\le0\forall x;-3\left(x+1\right)^2+12\le12\)
Vậy GTNN D là 12 <=> x + 1 = 0 <=> x = -1